The approach of family medicine in the management of patient with Recurrent Nummular Eczema Relapse - Gilbert Alfredo Delano Lonan; Sismei Dini Yufi; Eric Eric; Zita Atzmardina (Institute of Computer Science (IOCS), 2023)
At the Legok Health Center, the total number of dermatitis cases was 14 in August 2022. Mr. A is one of the patients who suffered from recurrent nummular eczema. He was the reason for conducting the visit. Diagnosis and management were carried out using a family medicine approach. Primary data was obtained through anamnesis, physical examination, and home visits. Secondary data was sourced from patient medical records at the Legok Health Center. Mr. A is 18 years old and has complained of a red sore on the left calf since one month ago. On physical examination, plaques were found in the left femur region and brachii sinistra et antebrachia dextra, localized distribution, colored erythema to hyperpigmentation, lenticular to numeric sizes, arranged in multiples with a circadian configuration, and well demarcated. The patient's internal factors are the lack of knowledge about the disease, the behavior that was often injured, stress, and loneliness. External factors included a lack of family knowledge about the patient's illness, the absence of regular visits from nearby health workers, and inadequate home ventilation. As the family approach was taken, there have been improvements in patient complaints, with the number of wounds complained by patients starting to thin out. The family medicine approach was carried out as a whole for individuals and families by applying the medical, behavioral, and social sciences principles. Individual management is an intervention in clinical aspects and a solution to environmental problems affecting personal health.